PENGARUH PEMBIAYAAN BERMASALAH DAN EFISIENSI OPERASIONAL TERHADAP PROFITABILITAS UNIT PENGELOLA KEGIATAN KECAMATAN SEJANGKUNG PERIODE 2018-2022 - azura, azura (Cross-Border Journal of Business Management, 2024)
This research was motivated by the gap between theory and practice, this happened in 2020 where the NPF ratio increased by 59.9% from the previous year of 23.94%. This also led to an increase in ROA of 5.92% from the previous year of 4.63%, supposedly if NPF increases then ROA will decrease. This is supported by a theory that explains that the higher the problematic financing, the lower the level of profitability of financial institutions. This research uses quantitative methods, the data used is secondary data, namely monthly financial statements for the 2018-2022 period obtained from the financial statement book of the Sejangkung Subdistrict Activities Management Unit. The data analysis method used is multiple linear regression analysis using classical assumption tests first, for data processing researchers use SPSS statistical test tool version 23. The hypothesis tests carried out are the coefficient of determination test, F test, t test and dominant test. The results of the study based on SPSS output show that problematic financing variables have a positive and insignificant effect on profitability and operational efficiency variables have a negative and significant effect on profitability. Meanwhile, simultaneously the variables of problematic financing and operational efficiency have a significant effect on profitability. The R Square obtained in this study amounted to 21.4% and the rest was influenced by other factors.